A Single-Center Experience With Total Percutaneous Implantation of a Low-Profile Thoracic Aortic Stent-Graft. (April 2023) - Benfor, Bright; Stana, Jan; Fernandez Prendes, Carlota; Pichlmaier, Maximilian; Mehmedovic, Aldin; Banafsche, Ramin; Rantner, Barbara; Tsilimparis, Nikolaos
Purpose: To evaluate the safety and effectiveness of total percutaneous implantation of the Zenith Alpha Thoracic (ZTA) endograft in the treatment of diseases of the descending thoracic aorta. Materials and Methods: A retrospective cohort study of 56 consecutive patients undergoing total percutaneous ZTA implantation between 2018 and 2020 was performed in a single center. Patients' demographics, clinical characteristics, anatomical parameters, operative details, device features, and postoperative outcomes were assessed. The primary endpoint was ongoing clinical success. A Cox regression model was used to determine the predictive factors of worse postoperative outcomes. Results: Eighty-three ZTA endografts were implanted in 35 men and 21 women with a mean age of 69±11 years for the treatment of 26 degenerative aneurysms, 15 type B dissections, and 8 penetrating ulcers, among others. Primary technical success was 100%, with a 30-day ongoing clinical success rate of 94.6%. The 1-year ongoing clinical success rate was 91.1% (51 patients), and freedoms from all-cause mortality, type 1 and 3 endoleaks, and any unplanned reintervention were, respectively, 95.3%, 91.4%, and 88.2% at 1 year. During follow-up, there was one case of surgical conversion for an aorto-esophageal fistula. On the contrary, neither aneurysmal rupture nor significant aneurysmal expansion was recorded. Repair of ruptured thoracic aorta and a high ratio of sheath outer diameter to external iliac artery diameter were found to be independently associated with worse outcomes, with adjusted odds ratios of 4.4 [1.5-15.3] and 4.9 [1.1-23.9], respectively. Conclusion: The outcomes of total percutaneous implantation of ZTA endograft show excellent primary technical success and favorable midterm ongoing clinical success. Factors associated with worse outcomes include the repair of ruptured aorta and a high sheath to access vessel ratio.